Organizational behavior - martin,john (Monographs of the Society for Research in Child Development ;, 1999)
Part 1 The world of organizational behaviour: managing organizational behaviour for quality and results; International organizational behaviour - managing across cultures; managing diversity - releasing every employee's potential. Part 2 Individual behaviour: individual differences, values and ethics; perception and attributions; motivation through needs, job design and satisfaction; motivation through equity; expectancy and goal setting; behaviour modification and self-management. Part 3 Group and social progress; group dynamics; power, politics and conflicts; individual and group decision making; team and teamwork; organizational communication processes; performance appraisal, feedback, and rewards; leadership; managing occupational stress. Part 5 The evolving organization: organizational structure and effectiveness; organizational life cycle and design; organizational change; managing change in learning organizations.